Analisis Pengaruh Variasi Produk, Harga Dan Tempat Terhadap Kepuasan Konsumen Pada Toko Sinar Baolang di Desa O’a Mate Kecamatan Alor Barat Laut Kabupaten Alor - Rahel Kabbi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effects of product variations, prices and places on customer satisfaction at Sinar Baolang Stores in O’a Mate Village, Northwest Alor District, Alor Regency. This type of research is a quantitative study with data collection, namely observation, questionnaires, interviews, and documentation study. The data is then analyzed using the t-test 10, 316 to determine the partial effect and the F-test 0,527 to determine the simultaneous effect on consumer satisfatction